Outsourcing performance implication of supplier manufacturer relationships and the perceived impact of environmental dynamism in Malaysia electrical and electronic industry - Hassan, Mohamad Ghozali; Razalli, Mohd Rizal; Abdullah, Rohani; Johari, Nor Azmi (2012)
This study used the partial least squares (PLS) and structural equation modeling (SEM) tool to examine the implication of supplier manufacturer relationships and the perceived impact of environmental dynamism of outsourcing performance in Malaysian electrical and electronic industry.This study also examined the perceived impact of environmental dynamism as moderating variables.The result indicated that the two dimension of the environmental dynamism which are customer demand and market competition do not moderate the relationship between relational oriented exchange (ROE) and outsourcing success.However, customer demand is supported as an independent variable to represent the outsourcing performance implication of supplier manufacturer relationships.The details of theoretical and practical implications of the findings are discussed.